The Reclamation of an Arabian Tradition: Using Oral History to Teach Humanities and Social Sciences in Saudi Arabia. Issue 2 (2nd July 2020) - Strachan, Laura; Winkel, Carmen
ABSTRACT: For more than thirty years, collecting oral histories has been recognized as an effective teaching strategy in the West. Although it is rare in Gulf Cooperative Council (GCC) countries, the authors adopted it to bridge knowledge gaps they observed in their Saudi Arabian students. The reclamation of familial stories and tribal information using oral history methodologies reconnected students to their past while facilitating a unique learning experience. This paper describes how an oral history project was created for female undergraduate students in Saudi Arabia to help them move beyond the hard science approach supported in the Arabian world to one that embraces a narrative-based methodology. Historically, oral histories – an important pillar of Arabian society – were used to transfer significant tribal information, customs, traditions, and stories from one generation to the next. Since the discovery of oil, the kingdom has undergone dramatic societal and lifestyle transformations resulting in the loss of some traditions. The fundamental goal for this project was to improve the students' comprehension of humanities and social science courses by reconnecting them to their past using historical methods.